Evaluation, Testing and assessment The 5th International scientific and practical conference “The world of science and innovation” - Hladkoskok, Lesia (Cognum Publishing House, London, United Kingdom., 2020)
The present article explores the ways in which evaluation, testing, and assessment are vital to education. Assessment is critical to understanding the strengths and needs of individual students. When delivered effectively, assessment outcomes can inform curriculum design and make learning more targeted and meaningful for each student.
Keywords: testing; evaluation; assessment; EFL (English as a Foreign Language); ESL (English as a second language).